The Crisis of New Criticism - Mojares, Resil B. (Silliman Journal, 2024)
This paper explores the limitations of New Criticism as a critical instrument in Philippine literature today. The introductory part of the paper traces briefly the development of the Formalist method and the important revisions of its scope in our time (Neo-Aristotelian Criticism, Mythographic Criticism, Historicism).